Chitosan mitigates salt stress in rice by enhancing antioxidant defense system - Khaleduzzaman, Md; Hossain, Mohammad Anowar; Bhuiyan, Muhammad Javidul Haque; Mahmud, Sakil; Tahjib-Ul-Arif, Md; Murata, Yoshiyuki (Fundamental and Applied Agriculture, 2021)
Salinity is one of the major constraints for rice (Oryza sativa L.) cultivation globally, as rice is highly sensitive to salinity than other cereal crops. In order to elucidate the improvement mechanism of salinity tolerance by chitosan (CS), we analyzed the morphological, biochemical and antioxidant enzymatic activities of salt-stressed rice at germination and seedling stages of four cultivars: BRRI dhan28 and BRRI dhan29 as salt-sensitive and Pokkali and Pengek as salt-tolerant. Salinity inhibited seed germination as well as growth of rice seedlings. At the germination stage, CS increased the germination percentage by enhancing amylase activity and signiﬁcantly accelerated shoot growth but not root growth under salt stress condition. In the seedling stage, 50 ppm of CS mitigated the growth inhibition of seedling of the sensitive cultivars and the reduction of chlorophyll (both chl ‘a’ and chl ‘b’) contents. Moreover, CS increased the activities of catalase (CAT) and ascorbate peroxidase (APX) but not the activities of peroxidase (POX). However, the accumulation of proline and phenols in the seedlings was increased under saline condition but not under saline condition supplemented with CS. Principal component analysis revealed that a relatively stronger association between 50 ppm CS treatment with the non-stress condition than that of 25 ppm CS treatment both in sensitive and tolerant cultivars which suggested that 50 ppm CS treatment was more effective. Our results suggest that exogenous CS can be used to mitigate salt-induced adverse effects in rice as well as in other crop plants.